Milk solids replacement with chickpea flour in a yogurt system and their impact on their physicochemical, rheological, and microstructural properties during storage (Scientia Agropecuaria, 2021)
Yogurt is one of the most widely consumed foods around the world, with a tendency to add several ingredients with functional properties. The incorporation of legume flours in food systems has been a growing trend in recent years. Therefore, this study evaluated the effect of the addition of chickpea flour on the physicochemical, rheological, and microstructural properties of yogurt. Different levels of chickpea flour (1, 2, and 3%) were added to yogurt and the evolution of systems were monitored on days 1, 8, 15, and 22 of storage. Results for pH (4.61 – 4.75), titratable acidity (0.58% - 0.72%) and density (1048 - 1139 kg/m3) showed no significant differences (p > 0.05), while higher concentrations of the flour resulted in lower levels of syneresis (15.90% - 23.73%). The flow properties confirmed the non-Newtonian behavior in the systems, fitting the two Power Law and Herschel-Bulkley models, thus establishing a relationship between the experimental data and the variables under study. The microstructure analysis showed that a higher concentration of chickpea flour increases the porosity of the system. Finally, the results suggest that it is highly recommended to replace milk solids with chickpea flour, thereby maintaining the properties and stability of the product.